Teknologi Budi Daya Varietas Padi Spesial di Lahan Sawah Irigasi - ikhwani, .; Rustiati, Tita (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2018)
Rice plants are strategically commodities as food supplied in Indonesia. The operated, provided, procurement and distribution under be incredibly important to food security, stability of national economy and to increased income of farmers. Rice In addition created to required rice as food / special functional. Needed production of rice that has added value (certain prices, nutrition scent, etc) or contained one or more components with particular physiological functions and useful for health. The development problems of rice with particular characteristics / special are reluctanced at farmers to planted or produced different between regions because it is dependent of climate, agroekosistem and the market. The experiment was aims to studied the cultivated technology of special rice variety at farmer’s lowland field, at the Cianjur district, West Java, in April – September 2016. The experiment was arranged as a split-split plot design with 3 replications. The main plot are fertilizer application, P1- the present local recomendation (45 kg N, Phonska ( 100 kg N, 125 kg P2O5 75 kg K2O; Pupuk organik (petrokimia) = 500 kg/ha), applied 1x at 14 days after transplanting. P2 – proposed recommended based on PHSL, 112,5 kg N dan Phonska (83,33 kg N, 104,2 kg P2O5 dan 62,50 kg K2O, applied 3 x at 7 dat, 21 dat and 42 dat (just before flower initiation stage). Sub plot: plant spacing T1 – a Legowo 2:1 (27 cm–50 cm x 13.5 cm); and T2 – legowo system 4: 1 ( 27cm - - 54 cm ) x 13,5 cm Sub-sub plot: special rice varieties V1- Cisokan,, V2- Inpari 21, V3- IR-42, V4- Lusi variety and V5 - Japonica rice (Tayken rice). The smallest plot (sub-sub plot) size was 4 m x 5 m, with the total number of plots was 60.Performance of the special rice varieties could be increased through optimalization of plant spacing and fertilizer application. The highest grain yields in the season was 9.80 ton grains/ha by Inpara 4 planted combination with jajar legowo 4:1 and the present local recommendation fertilizer, followed by Lusi variety (9.33 ton grains/ha) with combination the jajar legowo 4:1 and recommended based on PHSL, than Cisokan variety produced 9.24 ton grains/ha with combination legowo system 4: 1 and present local recommendation fertilizer. Application of fertilizer and plant spacing are significantly which were the highest yield. There was effected on yield produced . 8,50 ton grains/ha, at jajar legowo 4:1 planted highest 0,5 ton grains/ha than jajar legowo 2:1 produced 8,03 ton grains/ha.